Pengaruh Slow Deep Breathing dan Genggam Jari terhadap Nyeri Pasien Kanker Rektum RSUD Raden Mattaher Jambi - Regita Putri; Yosi Oktarina; Andika Sulistiawan; Dini Rudini; Andi Subandi (Universitas Nurul Jadid, 2026)
Pain is a major complaint in rectal cancer patients, significantly reducing quality of life. In addition to pharmacological therapy, pain management can be supported by non-pharmacological therapies such as slow deep breathing and finger grip therapy, but the effectiveness of their combination has been limitedly studied. This study aims to analyze the effect of combining these two therapies on pain in rectal cancer patients at Raden Mattaher Regional Hospital. Participants were assigned into intervention and control groups without randomization. The sample consisted of 40 respondents divided into 20 intervention groups and 20 control groups through a purposive sampling technique. Pain levels were measured using the Numeric Rating Scale (NRS) and Within-group differences were analyzed using Wilcoxon Signed Rank Test, while between-group differences were analyzed using Mann-Whitney test. The results showed that the average pain in the intervention group decreased from 4.80 to 2.40, while in the control group from 4.75 to 4.00. The Wilcoxon test showed a significant difference between the intervention group (p=0.000) and the control group (p=0.004), with a greater decrease in the intervention group. It was concluded that the combination of slow deep breathing and finger grip therapy was effective in reducing pain in rectal cancer patients.